A Clinical Trial Shows Improvement in Skin Collagen, Hydration, Elasticity, Wrinkles, Scalp, and Hair Condition following 12-Week Oral Intake of a Supplement Containing Hydrolysed Collagen - David M. Reilly; Liane Kynaston; Salma Naseem; Eva Proudman; Darcy Laceby (Dermatology Research and Practice)
Background. Hydrolysed collagen supplements are reported to fight the signs of aging and improve skin appearance, but more authoritative clinical evidence is needed to support efficacy. Aim. This randomised, double-blind, placebo-controlled study evaluated the efficacy of a supplement containing hydrolysed collagen and vitamin C (Absolute Collagen, AC) on biophysical parameters and visible signs of aging for skin, scalp, and hair, when taken daily or every 48 hours. Methods. We measured dermal collagen using confocal microscopy and high-resolution ultrasound. Hydration, elasticity, wrinkles, and clinical trichoscopy were measured in parallel to expert visual grading. Efficacy measures were recorded at baseline, week 6, and week 12. Results. Following 12 weeks daily use of the AC supplement, using confocal microscopy, we observed a significant 44.6% decrease in fragmentation vs. placebo (p<0.01). We also measured a change in the ultrasound LEP (low echogenic pixel) ratio comparing upper and lower dermis (−9.24 vs. −7.83, respectively, p=0.05), suggesting collagen improvements occurred more in the upper dermal compartment. After 12 weeks vs. placebo, skin hydration was increased by 13.8% (p<0.01), R2 elasticity index was increased by 22.7% (p<0.01), and Rz profilometry index was decreased by 19.6% (p<0.01). Trichoscopy showed an average 11.0% improvement in scalp scaling and a 27.6% increase in the total number of hairs counted vs. placebo (p=n.s.). This was associated with a 31.9% increase in clinical grading score for hair healthy appearance (p<0.01). Conclusion. The AC supplement has shown clinical benefits for skin, scalp, and hair, when used either daily or every 48 hours, over a 12-week period.